AKSI PENANAMAN MANGROVE DI PESISIR PANTAI LATERI – KOTA AMBON: PENDEKATAN PARTISIPATIF KADER AMGPM RANTING 1 LATERI DAN AMGPM RANTING CALVARY - Ronald Hukubun; Sherly Lewerissa; Laury Marcia Ch. Huwae (Universitas Mataram, 2026)
Mangrove planting is a crucial effort in the conservation and restoration of coastal ecosystems that are vulnerable to environmental degradation. This community service activity was carried out through mangrove planting along the coast of Lateri, Ambon City, using a participatory approach that involved youth cadres from the Maluku Protestant Church (AMGPM), specifically AMGPM Branch 1 Lateri and AMGPM Calvary Branch, as the main collaborators. The goal was to help preserve and sustain mangrove ecosystems, which are increasingly under threat. A total of 300 mangrove seedlings were successfully planted in a designated area that had been previously surveyed and jointly selected. The method used was participatory engagement, which included both the physical planting of mangrove seedlings and raising environmental awareness among AMGPM cadres and the surrounding community. The results of the activity indicated an increase in ecological awareness and community solidarity. Additionally, initial success was achieved in planting and maintaining the mangrove seedlings. The involvement of AMGPM cadres contributed to strengthening social responsibility and leadership among the younger generation. It is expected that this activity will serve as a model for participatory environmental initiatives that can be replicated in other areas, thereby enhancing the role of AMGPM cadres and youth in environmental conservation. Ultimately, this will support the sustainable management of mangrove ecosystems along the coast of Ambon Island.